Modification of cellulose acetate membranes with graphene oxide nano-fillers for water treatment - Mahmmod, Madina (AUC Knowledge Fountain, 2017)
The aim of this study is to prepare membranes composed of CA and GO for water purification. Cellulose acetate (CA) (Mw = 52,000 Da) membranes containing different amounts of graphene oxide (GO) were prepared by phase inversion (PI). Acetone was used as a solvent and N, N- dimethylformamide (DMF) as a non-solvent, with a ratio of 4:1, and deionized water as the coagulation medium. The membranes were prepared using a mixture of 19 wt.% CA with 0.025 to 0.1 wt.% GO. The effect of GO on membrane characteristics was investigated by scanning electron microscopy (SEM), Brunauer-Emmett-Teller surface analysis (BET) and contact angle measurements. Salt rejection and permeation rates were tested using a 2000 ppm NaCl solution and 5000 ppm MgSO4 solution at a pressure of 24 bars using a dead-end filtration cell. SEM cross sectional images showed uniform dispersion of GO sheets in the polymeric matrix which implies the formation of strong hydrogen bonds between CA and GO sheets. An increase in the number and sizes of the pores of CA/GO membranes in comparison with blank CA membranes was also noticed. In addition, finger-like macropores were formed indicating the instantaneous solvent-non-solvent exchange as a result of the hydrophilic nature of GO added. This was supported by the gradual decrease in the contact angle measurements from 75o to 61o with increasing GO content from 0 to 0.1 wt.%. It was found that permeation rates increased with increasing GO content. The addition of 0.025 wt.% and 0.05 wt.% GO improved 2000 ppm NaCl permeation by 64% and 95% respectively when compared with CA membrane. An increase in permeation by 106%, as compared to the CA membrane when 0.1 wt.% GO was added, was observed. It is believed that this increase in GO content increased the number of hydrophilic sites in the membranes which attracted water molecules and facilitated their movement through the membrane. As for salt rejection, the membrane with 0.05 wt.% GO showed the highest salt rejection value of 74% and 81% for 2000 ppm NaCl and 5000 ppm MgSO4 solutions respectively. This was explained by the increase in the total surface area of micropores with width less than 2 nm. However, on increasing GO content to 0.1 wt. %, blocking of the micropores occurred leading to a decrease in the salt rejection values to 23% and 11% for 2000 ppm NaCl and 5000 ppm MgSO4 solutions respectively. This work demonstrates that CA/GO membranes outperform traditional CA membranes due to their improved permeation and salt rejection behavior and therefore have great potential in the field of water purification.